Concomitant Percutaneous Coronary Intervention and Transcatheter Aortic Valve Replacement: Safe and Feasible Replacement Alternative Approaches in High‐Risk Patients with Severe Aortic Stenosis and Coronary Artery Disease. Issue 5 (21st July 2013) - Salhab, Khaled F.; Al Kindi, Adil H.; Lane, James H.; Knudson, Kathleen E.; Kapadia, Samir; Roselli, Eric E.; Tuzcu, Murat E.; Svensson, Lars G.
Abstract Objective Transcatheter aortic valve replacement (TAVR) is performed as a stand‐alone procedure in patients that are not suitable for surgical aortic valve replacement. However, a significant proportion of patients with severe aortic stenosis have coexisting coronary artery disease (CAD). We report concomitant TAVR and percutaneous coronary intervention (PCI) as a single procedure in such patients. Methods Three patients with severe aortic stenosis and CAD that were high risk for conventional surgery had concomitant alternative approach TAVR and PCI performed. Two patients had PCI and stent placement immediately after the deployment of the transapical transcatheter aortic valve, and one patient had a coronary artery stent placed just prior to the deployment of the transaortic transcatheter aortic valve. Results Two male patients and one female (age range 68–91 years) had 100% procedural success with resolution of symptoms and zero residual stenosis. There were no complications related to neurologic events, worsening renal function, or myocardial infarction. In‐hospital and 30‐day mortality was zero. All three patients were discharged home with a median hospital stay of eight days. Conclusions In our small series of patients presented we demonstrate that PCI and TAVR performed concurrently in the hybrid operating room is a feasible option in patients undergoing TAVR with coexisting CAD. Furthermore, we propose this single‐stage approach in such high‐risk patients as it decreases the number of procedures performed and may theoretically lower cost and hospital stay. doi: 10.1111/jocs.12176 (J Card Surg 2013;28:481–483)